Non-Lethal Assessment of Potentially Toxic Elements Across Mammalian Trophic Levels in African Savannahs - Webster, Andrea B.; Callealta, Javier F.; Bennett, Nigel C.; Ganswindt, Andre (Frontiers in Environmental Science, 2022)
South Africa is one of the most diverse countries in the world but the increase in agricultural, industrial and technological development to meet the needs of the growing human population has led to increased amounts of potentially toxic elements (PTEs) and other chemicals in the environment. As regional and global environmental processes influence local conditions to differing degrees, all organisms within a specific environment are exposed to highly complex, ill-defined PTE and chemical mixtures. Differences in feeding strategies within and between vertebrate trophic levels are likely to influence the degree to which individuals may be exposed to and affected by PTE presence. Using vertebrate faeces as a biological matrix, we investigate and compare quantitative differences of PTEs in herbivorous, omnivorous and carnivorous terrestrial vertebrates from two protected areas in South African savannah. Of the eleven PTEs assessed [aluminium (Al), arsenic (As), barium (Ba), cadmium (Cd), chromium (Cr), mercury (Hg), lead (Pb), antimony (Sb), tin (Sn), strontium (Sr) and vanadium (V)], the highest concentrations of Al, As, Cr, Pb, Sn and V were found in carnivores. General patterns were evident between groups at each site for specific elements, but absolute values for the same elements were site-specific. This is the first study to non-invasively examine and compare PTE concentrations in a variety of free-ranging mammalian wildlife occupying different trophic levels within South African protected areas. Our results confirm that all individuals across trophic levels within these sites are exposed to multiple and varied PTE mixtures on a continuous basis. Whether PTEs at these concentrations cause synergistic or antagonistic disruption of physiological and biological systems alone or in combination in free-ranging African wildlife species is still unclear and requires further investigation.